The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1981-863720200003320190049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music on reducing anxiety in children during dental treatment

Abstract: Objective: The objective of this study was to evaluate the impact of music on anxiety in children during dental care Methods: A total of 40 children 5 to 11 years old were selected; they were randomized into 2 groups (n = 20): group 1: experimental, children were subjected to music therapy; group 2: control, children were not subjected to music therapy. We measured oxygen saturation, heart rate and levels of Corah anxiety scale and pain scale. The results for heart rate were evaluated by ANOVA. The Kruskal Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
1
7
0
6
Order By: Relevance
“…A total of 12 articles [ 20 , 21 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ], including 1028 patients, were included. Meta-analysis showed no significant difference in heart rate between the experimental and control groups preoperatively (I 2 = 39.5%, WMD (95% CI): −0.98(−2.07, 0.12), p = 0.08); postoperatively, music therapy significantly reduced heart rate in patients with dental anxiety (I 2 = 81.2%, WMD (95% CI): −7.33(−10.07, 4.58), p < 0.0001), and further meta-regression showed that different study populations (children or adults, p = 0.32), different oral operations ( p = 0.32), different countries ( p = 0.13), and different years ( p = 0.32) did not significantly affect the results of this study ( Figure 3 , Supplementary Files S2–S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 articles [ 20 , 21 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ], including 1028 patients, were included. Meta-analysis showed no significant difference in heart rate between the experimental and control groups preoperatively (I 2 = 39.5%, WMD (95% CI): −0.98(−2.07, 0.12), p = 0.08); postoperatively, music therapy significantly reduced heart rate in patients with dental anxiety (I 2 = 81.2%, WMD (95% CI): −7.33(−10.07, 4.58), p < 0.0001), and further meta-regression showed that different study populations (children or adults, p = 0.32), different oral operations ( p = 0.32), different countries ( p = 0.13), and different years ( p = 0.32) did not significantly affect the results of this study ( Figure 3 , Supplementary Files S2–S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Em outro estudo que avaliou o impacto da música como redutor de ansiedade no atendimento odontológico de crianças, demonstrou redução significante na frequência cardíaca nas crianças que escutaram música durante o atendimento odontológico. No grupo sem música, a frequência cardíaca manteve-se inalterada durante todo o atendimento (Tshiswaka & Pinheiro, 2020). Outro estudo avaliou o efeito de uma intervenção musical sobre a ansiedade e parâmetros vitais em 60 pacientes com idade igual ou superior a 18 anos com doença renal crônica em comparação ao cuidado de clínicas de hemodiálise, concluiu que o estímulo musical infere ter potencial de intervenção para a redução do estado de ansiedade durante sessões de hemodiálise (Melo et al, 2018).…”
Section: Discussionunclassified
“…Adults (n=6; 33.3%) and preterm/ premature infants (n=6; 33.3%) constituted 66.7% of the studies, children and adolescents (n=5) held 27.8% of studies; while one study was conducted with full-term newborns (n=1; 5.5%). For assessing the efficacy of music therapy on oxygen saturation level, most of the adult studies (66.7%) (Handan E et al, 2018;Nilsson U, 2009;Nilsson U et al 2005;Saritas et al 2016) were concerned with pre-intra-and post-operative procedures while other two papers addressed terminally ill patients (Antoniazza B et al, 2018) and ICU patients with head injury (Indriani, N. at al., 2018); three research papers (Dixit UB et al, 2020;Marwah N et al, 2005;Tshiswaka SK et al, 2020) concerning children and adolescents recounted using music therapy pre-, intra-and posttreatment for dental anxiety while two studies (Calcaterra, Valeria et al, 2014;Atiye Karakul et al, 2018) used the music during the recovery period after daycare surgery.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Two papers concerning adult patientsone in ICU with head injury (Indriani, N. et al, 2018) and another (Antoniazza B et al, 2018) with terminally ill patients stated statistically significant outcome where oxygen saturation level raised with music therapy. Out of these nine studies concerning surgery/ treatment, ones that did not find music therapy effective include one study with adult patients undergoing open hernia operation (intra and post-) (Nilsson U et al, 2005); three studies (Dixit UB et al, 2020;Marwah N et al, 2005;Tshiswaka SK et al, 2020) with children undergoing dental treatment (intra-) and two (Calcaterra, Valeria, et al, 2014;Atiye Karakul et al, 2018) with children and adolescents undergoing day care surgery (post-). Two (Jabraeili M et al, 2016;Elham Shafiei et al, 2020) out of six (33.3%) studies concerning preterm and premature infants had shown a positive effect of music therapy on oxygen saturation levels while four (66.7%) studies (Eskandari N et al, 2013;Cristiane Aparecida Moran et al, 2015;Diler Aydin et al, 2012;Aydın, D. et al, 2014) did not find music therapy effective for improvement of oxygen saturation level.…”
Section: The Outcome Of Music Therapy On Oxygen Saturation Levelmentioning
confidence: 99%